DNA Methylation in CYP82E4 Regulates Nicotine Conversion of Nicotiana tabacum - Wang, Yaqi; Zhang, Xingzi; Zhang, Fang; Cheng, Lirui; Jiang, Caihong; Yang, Aiguo; Li, Fengxia (Plant, cell and environment, 2025)
ABSTRACT Nornicotine content is very low in tobacco, accounting for less than 5% of total alkaloids. Nicotine conversion refers to the process by which nornicotine is synthesised spontaneously and in large quantities from nicotine. CYP82E4 is the only key enzyme gene involved in nicotine conversion, but it is unclear by what mechanism plants regulate the expression of this gene and thus change the phenotype of nicotine conversion. By comparing single‐base resolution DNA methylomes of senescent leaves from NC‐L and its high converter variant NC‐H, we found two differentially methylated regions (DMRs) in CYP82E4 of NC‐H. The bisulfite sequencing PCR (BSP) assay demonstrated that the DNA methylation levels in two specific segments of CYP82E4 were 39%–52% lower for NC‐H than for NC‐L. Furthermore, treatment with the DNA methylase inhibitor 5‐azacitidine resulted in a decrease in DNA methylation levels of CYP82E4 and the change of nicotine conversion phenotype from norconverter tobacco to high converter tobacco. Similarly, the MET1 mutation significantly reduced the DNA methylation level of CYP82E4 and transformed the nicotine conversion phenotype. These findings suggest that DNA methylation plays a crucial regulatory role in nicotine conversion, with decreased methylation levels in CYP82E4 being significant factors in nicotine conversion. Summary statement Nicotine conversion promotes the formation of carcinogen N‐nitrosonornicotine, so it is undesirable in tobacco. But it is not clear why nicotine conversion occurs. In this study, we elucidate DNA methylation plays a crucial regulatory role in nicotine conversion, with decreased DNA methylation levels in CYP82E4 being significant factors.